2014
DOI: 10.1016/j.neuroscience.2013.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous intrinsic excitability of murine spiral ganglion neurons is determined by Kv1 and HCN channels

Abstract: The spiral ganglion conveys afferent auditory information predominantly through a single class of type I neurons that receive signals from inner hair cell (IHC) sensory receptors. These auditory primary afferents, like in other systems (Puopolo and Belluzzi, 1998, Gascon and Moqrich, 2010, Leao et al., 2012) possess a marked diversity in their electrophysiological features (Taberner and Liberman, 2005). Consistent with these observations, when the auditory primary afferents were assessed in neuronal explants s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 68 publications
6
38
1
Order By: Relevance
“…Compared to V h ranging from −65 to −90 mV in these neurons, V h in SGNs is at least 10 mV more negative, and as a result, only 3 % of I h should be present at rest. When blocked by Cs + , this amount of I h is shown to hyperpolarize the RMP by 4 mV (Liu et al 2013). These results are consistent with those recordings made ex vivo from the nerve terminals (Yi et al 2010).…”
Section: Functional Significancesupporting
confidence: 88%
See 2 more Smart Citations
“…Compared to V h ranging from −65 to −90 mV in these neurons, V h in SGNs is at least 10 mV more negative, and as a result, only 3 % of I h should be present at rest. When blocked by Cs + , this amount of I h is shown to hyperpolarize the RMP by 4 mV (Liu et al 2013). These results are consistent with those recordings made ex vivo from the nerve terminals (Yi et al 2010).…”
Section: Functional Significancesupporting
confidence: 88%
“…While a portion of the mechanism contributing to the threshold variation is based on synaptic mechanisms (Liberman et al 2011;Wong et al 2013), it is also possible that adjustment of the neuronal excitability post-synaptically could play a role. We recently found that spiral ganglion neuron firing thresholds are largely controlled by K v 1 potassium channels, while a negative V h of I h seems to prevent neurons with the lowest voltage threshold from spontaneous firing (Liu et al 2013). Consistent with this mechanism, modulation of I h by cAMP produces a positive shift in V h that enhances neural excitability and spontaneous discharge in superior olivary complex neurons (Shaikh and Finlayson 2005) in vivo.…”
Section: Functional Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics of both channel types operate at slower timescales than the Hodgkin-Huxley channels (Rothman and Manis 2003;Liu et al 2014b). KLT channels are responsible for increasing the cell's voltage threshold and hyperpolarizing the resting membrane potential (Liu et al 2014a). HCN channels are well known for being permeable to Na + and K + with ratios ranging from 1:3 to 1:5 (Biel et al 2009).…”
Section: Mechanisms and Modelsmentioning
confidence: 99%
“…When HCN is activated under membrane hyperpolarization, this generates a dominant inward Na + current which helps return the membrane potential back towards rest. HCN channels contribute to stabilizing the resting membrane potential of SGNs (Liu et al 2014a;Liu et al 2014b), a function that HCN appears to fulfill in a range of different cell types (Robinson and Siegelbaum 2003;Howells et al 2012;Benarroch 2013). An interesting property of the current produced by HCN channels, known as I h , is that it can increase the neuron's firing by a rebound excitation which happens towards the end of a hyperpolarizing pulse (Chen 1997).…”
Section: Mechanisms and Modelsmentioning
confidence: 99%